Essential forensic pathology : core studies and exercises - Corrigan, Gilbert Edward (Boca Raton, Fla. : CRC Press, 2012)
"A thorough and unique reference, this text is ideal for those entering the field of forensic pathology. Beginning with a brief review of the essentials, the book outlines 15 different sets of learning experiences available to a trainee. Providing comprehensive coverage of causes and modes of death, the book focuses on 40 autopsy experiences through which the forensic pathology resident is likely to rotate. For each topic, the chapters provide an emphasis on the objective to be reached and include discussion questions as a guide"--Provided by publisher.
section 1. Introduction -- section 2. A program in forensic pathology -- section 3. Forensic pathology essentials -- section 4. Dedication.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Forensic pathology -- Problems, exercises, etc; Electronic books